2019
DOI: 10.1080/00380768.2019.1649976
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dry-wet cycles on carbon dioxide release from two different volcanic ash soils in a Japanese temperate forest

Abstract: In the present study, two volcanic ash soils (soil A and B) from a temperate broad-leaved forest in eastern Japan were aerobically incubated under repeated dry-wet cycles and continuously constant moisture conditions. The primary aims were to quantify the potential for enhancement of carbon dioxide (CO 2 ) release owing to increased water fluctuation and to examine differences in the responses of volcanic ash soils with different physicochemical properties. Soil B, rather than soil A, was a typical Andosol. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…Using two Luvisols from French long-term field experiment sites, Kpemoua et al (2023) also showed similar features of changes in CO 2 release associated with DWCs, indicating the need for further comparison of CO 2 release between DWCs and constant moisture conditions with the same mean water content. In contrast to these studies, Nagano et al (2019) found a 49% increase in CO 2 release rate associated with DWCs in an Andisol collected from a Japanese forest, and this increase was more than double that of another non-volcanic ash soil from the same forest. Therefore, there are substantial variations in trends of effects of DWCs in comparison with constant moisture conditions with the same mean water content during incubation, and knowledge gaps remain about environmental and soil predictors for variations in effect sizes.…”
Section: Introductioncontrasting
confidence: 79%
See 3 more Smart Citations
“…Using two Luvisols from French long-term field experiment sites, Kpemoua et al (2023) also showed similar features of changes in CO 2 release associated with DWCs, indicating the need for further comparison of CO 2 release between DWCs and constant moisture conditions with the same mean water content. In contrast to these studies, Nagano et al (2019) found a 49% increase in CO 2 release rate associated with DWCs in an Andisol collected from a Japanese forest, and this increase was more than double that of another non-volcanic ash soil from the same forest. Therefore, there are substantial variations in trends of effects of DWCs in comparison with constant moisture conditions with the same mean water content during incubation, and knowledge gaps remain about environmental and soil predictors for variations in effect sizes.…”
Section: Introductioncontrasting
confidence: 79%
“…We collected 10 soil samples from depths of 0-5 cm or 0-10 cm in six forests and a pastureland located in Niigata (six soils from four forests), Ibaraki (two soils from a forest) (Nagano et al, 2019), and Oita (two soils from a forest and a pastureland) (Wijesinghe et al, 2021) prefectures in Japan. Figure 1 and Table 1 present the locations and site characteristics, i.e., elevation, mean annual temperature (MAT), mean annual precipitation (MAP), potential evapotranspiration (PET), and net primary production (NPP).…”
Section: Site Description and Soil Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…These soils were originally sampled to investigate the environmental distribution of radioactive cesium that was affected by the Fukushima nuclear accident (Atarashi-Andoh et al, 2021) and have been stored in air-dried conditions. The soils were heterogeneously affected by volcanic ash during their development, with various physiochemical and mineralogical properties and C dynamics within a single water catchment (Suzuki, 2002;Nagano et al, 2019). Assuming that WEOM from air-dried soils was derived from soil microbial bodies (Marumoto et al, 1977(Marumoto et al, , 1982Marumoto, 1984;Unger et al, 2010Unger et al, , 2012Kaiser et al, 2015), we expected that the enrichments of 13 C and 15 N in WEOM relative to the bulk soils would be correlated with the concentrations of organomineral complexes and short-range order minerals (non-crystalline oxyhydroxides of aluminum and iron, allophane, imogolite, and allophane-like constituents; Imaya et al, 2007), which likely control the SOM stability and thus their availability to soil microbes (Johnson et al, 1995;Baldock and Skjemstad, 2000;Asano and Wagai, 2014;Takahashi and Dahlgren, 2016;Rasmussen et al, 2018;Wagai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%